Integrating adult learning and technologies for effective education : strategic approaches - Wang, Victor C. X. (Hershey, PA : Information Science Reference, 2010)
'This book provides relevant theoretical frameworks and the latest empirical research findings in the area of integrating adult learning and technology, exploring different innovative and strategic instructional approaches'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Adult education -- Computer-assisted instruction; Internet in education